Socio-spatial dimensions in energy transitions: Applying the TPSN framework to case studies in Germany. (September 2020) - Gailing, Ludger; Bues, Andrea; Kern, Kristine; Röhring, Andreas
Energy transitions cannot be fully grasped without appreciating their spatial implications. This paper takes up the idea of conceptualizing the socio-spatial dimensions of energy transitions and examines the respective value of the Territory, Place, Scale, and Network (TPSN) framework. The fundamental contribution of this framework is to move the focus of the debate away from whether one ontology of the socio-spatial is 'better' than another. By applying the TPSN framework to emblematic cases of regional energy spaces in Germany, we realized that the dynamics of different fields of action within an energy transition are characterized in each case by a specific pattern of the four socio-spatial dimensions and related strategies. The paper concludes with a discussion of the benefits and the shortcomings of the framework as it relates to understanding energy transitions. The fundamental role of place-making at a nexus with territorializations, as well as the additional importance of networking and rescaling strategies, are to be understood with the additional factors of the role of governance spaces, the upscaling of local experiments, powerful space-related discourses, and the socio-materiality of spaces.